Complementarity of neutron reflectometry and ellipsometry for the study of atmospheric reactions at the air–water interface. Issue 129 (17th December 2015) - Sebastiani, Federica; Campbell, Richard A.; Pfrang, Christian
Abstract : The combined application of neutron reflectometry and ellipsometry to determine the oxidation kinetics of organic monolayers at the air–water interface is described for the first time. Abstract : The combined application of neutron reflectometry (NR) and ellipsometry to determine the oxidation kinetics of organic monolayers at the air–water interface is described for the first time. This advance was possible thanks to a new miniaturised reaction chamber that is compatible with the two techniques and has controlled gas delivery. The rate coefficient for the oxidation of methyl oleate monolayers by gas-phase O3 determined using NR is (5.4 ± 0.6) × 10 −10 cm 2 per molecule per s, which is consistent with the value reported in the literature but is now better constrained. This highlights the potential for the investigation of faster atmospheric reactions in future studies. The rate coefficient determined using ellipsometry is (5.0 ± 0.9) × 10 −10 cm 2 per molecule per s, which indicates the potential of this more economical, laboratory-based technique to be employed in parallel with NR. In this case, temporal fluctuations in the optical signal are attributed to the mobility of islands of reaction products. We outline how such information may provide critical missing information in the identification of transient reaction products in a range of atmospheric surface reactions in the future.